The encrypted verbivocovisuality of Augusto de Campos - Paula, Luciane de [UNESP]; Batista, Rafaela dos Santos [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2021)
This article reflects on Augusto de Campos' poetics. For this, it is guided by the aesthetic conception employed by him and other concretists as a project of concrete poetry: verbivocovisuality. The objective is to relate this perception with the Bakhtinian philosophy of the language regarding the notion of language, understood as three-dimensional. The hypothesis is that the authorial understanding of the Noigandres group and that of the Russian Circle converge, each with them own peculiarity, with respect to the language perspective. The significance of this reflection is found in the theoretical advance in the Bakhtinian field. The methodology used is dialectic-dialogical. The concepts of language, enunciation, dialogue, subject, ideology and social voices underlie the discussion. The relevance turns to the contemporary study of language. The results reveal the productivity of the Bakhtinian philosophical proposal in contemporaneity, especially about a verbivocovisual perspective to (concrete) language.
Keywords: Concrete Poetry; Bakhtin Circle; Philosophy of the language